2022
DOI: 10.1093/cercor/bhac303
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural features of L2/3 pyramidal cells continuously covary with pial depth in mouse visual cortex

Abstract: Pyramidal cells of neocortical layer 2/3 (L2/3 PyrCs) integrate signals from numerous brain areas and project throughout the neocortex. These PyrCs show pial depth-dependent functional and structural specializations, indicating participation in different functional microcircuits. However, whether these depth-dependent differences result from separable PyrC subtypes or whether their features display a continuum correlated with pial depth is unknown. Here, we assessed the stimulus selectivity, electrophysiologic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Consistent with this idea, we found that the excitability of binocular neurons was negatively correlated with the strength of both callosal and ipsilateral eye input. These data are consistent with recent studies which suggest that L2/3 pyramidal neurons in the superficial layers of binocular V1 are organized as a continuum and show a gradient in terms of their molecular (Cheng et al, 2022;Kim et al, 2020;Tan et al, 2020) and electrophysiological properties (Weiler et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this idea, we found that the excitability of binocular neurons was negatively correlated with the strength of both callosal and ipsilateral eye input. These data are consistent with recent studies which suggest that L2/3 pyramidal neurons in the superficial layers of binocular V1 are organized as a continuum and show a gradient in terms of their molecular (Cheng et al, 2022;Kim et al, 2020;Tan et al, 2020) and electrophysiological properties (Weiler et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, in around 30% of cells using 3 µM muscarine, only an ADP with no spiking was observed. This variability might be due to heterogeneity in the tested sample of cells, perhaps reflecting subsets of cells with different sets of channels or receptors (Luo et al ., 2017; Karimi et al ., 2020; Weiler et al ., 2023). The probability of generating a spiking PP was also greatly dependent on the concentration of muscarine used ( Figure 2C ).…”
Section: Discussionmentioning
confidence: 99%
“…The recordings were made in alert but passively behaving subjects, and could yet be consistent with an intrinsic modulatory role, in contrast to FF neurons in layer 3 with better capability to transmit specific, focal image features. Layer 2 also showed significantly higher spontaneous activity, perhaps consonant with a couple of electrical characteristics of neurons in layer 2 of mouse V1 -higher membrane input resistance and longer time constants -as noted by Weiler et al (2023). Whilst, therefore, FB precision signalling finds an initial, if tenuous foothold in generic physiology, the nature of FF error signalling is more securely rooted in well-documented aspects of cellular electrophysiology and neural dynamics (Section 3.3).…”
Section: Precisionmentioning
confidence: 71%
“…By comparison, pyramid neurons lying more superficially are observed to have more profuse apical arborisations in layers 1 and 2. Of note, a corresponding continuum has been quantitatively documented in layer 2/3 of mouse V1, where pyramid neurons lying more superficially receive progressively less input from layer 4, and have progressively broader apical dendritic trees ( Weiler et al, 2023 ). In macaque V2, layer 3B houses the forward pathway, posited to comprise EXP and ERR pyramid neurons.…”
Section: Generic Physiologymentioning
confidence: 96%